Comparison of salivary interleukin-6, interleukin-8, C - reactive protein levels and total antioxidants capacity of obese individuals with normal-weight ones - Safabakhsh Deniz; Jazaeri Mina; Abdolsamadi Hamidreza; Abassi Ebrahim; Farhadian Maryam (Sciendo, 2022)
Objective: Obesity is a worldwide concern that may lead to type 2 diabetes, cardiovascular diseases, etc. Several serum biomarkers have been identified in the saliva of obese individuals, including inflammatory cytokines, adipokines, insulin, and cortisol. The present study aimed to compare salivary interleukin-6 (IL-6), interleukin-8 (IL-8), C-reactive protein (CRP) levels and total antioxidants capacity (TAC) of obese individuals with normal-weighted ones.